Potential of Gingerol in Emprit Ginger Extract (Zingiber officinale var. amarum) as a Biopesticide to Control Caterpillars (Crocidolomia pavonana) - Tathe Surya Ananda; Maria Marina Herawati; Ruth Meike Jayanti (Universitas Muhammadiyah Palembang, 2026)
Crocidolomia pavonana is a major pest that damages Brassicaceae plants such as cabbage, mustard greens, and broccoli. Continuous use of synthetic pesticides can cause pest resistance. This study aims to evaluate the acute toxicity and potential of Jahe Emprit (Zingiber officinale var. amarum) extract which is rich in gingerol as a botanical biopesticide against the third instar larvae of Crocidolomia pavonana, which is one of the main pests of Brassicaceae plants. This study was conducted using an experimental method with a Randomized Block Design (RBD) using four extract concentration treatments, namely 2%, 4%, 6%, and 8%, and used a negative control in the form of distilled water and a positive control pesticide Fenite 150 OD. Analysis of the active compound gingerol in the extract was carried out using High-Performance Liquid Chromatography (HPLC). The extract mortality test was carried out to determine Lethal Time 50 and Lethal Concentration 50 through the Topical Application method. The results of HPLC analysis of the bioactive gingerol compound showed a high level of 8.082 µg/mL. Mortality tests showed a significant increase in larval mortality along with increasing concentration and duration of exposure. The (LC50) value was recorded at 4.52%, indicating that the extract has a fairly high potential for acute toxicity. However, based on the (LT50) value of 60.26 hours (±2.5 days), this extract is included in the category of insecticides with a slow-acting mechanism, which is a typical characteristic of plant secondary metabolites. The most efficient extract concentration, namely 8%, was able to produce mortality of up to 70% and efficacy of 66.70% after 72 hours of treatment. The novelty of this research is the use of standardized ginger extract with verification of gingerol content through HPLC as a basis for biopesticide development., providing an alternative for sustainable pest control, and supporting environmentally friendly agricultural practices.